MBRS-21. CLINICAL AGGRESSIVENESS OF TP53-WILD TYPE SONIC HEDGEHOG MEDULLOBLASTOMA WITH MYCN AMPLIFICATION. (4th December 2020) - Mitani, Yuichi; Fukuoka, Kohei; Matsushita, Yuko; Hibiya, Yuko; Honda, Satoko; Mori, Makiko; Arakawa, Yuki; Ichimura, Koichi; Kobayashi, Masao; Tanami, Yutaka; Nakazawa, Atsuko; Kurihara, Jun; et al.
Abstract: Clinical implication of MYCN amplification in sonic hedgehog (SHH) medulloblastoma may still be controversial due to the frequent co-occurrence with TP53 mutation, which is one of the poorest prognostic factors among the subgroup. We described two cases of TP53-wild type SHH medulloblastoma with MYCN amplification, showing dismal clinical course with rapid disseminated relapse just after the end of treatment. CASE 1: A 7-year-old boy developed a non-metastatic cerebellar tumor. Pathology of the tumor was consistent with classic medulloblastoma. The patient received treatment that involved reduced-dose (18 Gy) craniospinal irradiation (CSI), local irradiation, and chemotherapy. However, sudden respiratory arrest developed due to massive intracranial disseminated relapse 9 months after the initial surgery. CASE 2: A 6-year-old boy presented a large mass in his 4 th ventricle without dissemination. He diagnosed with large cell/anaplastic medulloblastoma and underwent radiation therapy (24 Gy of CSI and local irradiation) and chemotherapy, followed by high-dose chemotherapy. However, dissemination through neuroaxis occurred 9 months after the diagnosis. Methylation data of the cases was entered into a recently published classifier and both tumors were classified as "medulloblastoma, subclass SHH A (children and adult)". Copy number analysis demonstrated MYCN amplification in both cases. TP53 mutation analysis from exon 2 to 10 indicated wild type in one case. Additionally, p53 immunochemistry in both cases also indicated wild type. The cases remind us of the clinical aggressiveness of SHH medulloblastoma with MYCN amplification, even if there is no TP53 mutation. The tumor should still be treated with the most intensified treatment.